The Contribution of Behavior Accounting with the Sakinah Finance Approach to the Financial Management of Islamic Families - Rifatul Muawanah; Diniyah Sukma; Ahmad Zuhril Kalam; Eny Latifah (Institut Agama Islam Negeri Padngsidimpuan, 2021)
Abstrak Tujuan penelitian ini adalah untuk mengetahui perilaku akuntansi dengan pendekatan Sakinah Finance dan nilai-nilai ekonomi Islam dalam keluarga Islam. Penelitian ini menggunakan metode deskriptif kualitatif dengan menggunakan analisis data triangulasi dengan menggabungkan wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini adalah keluarga Islam mampu menerapkan Behavior Accounting dengan mencatat semua transaksi keuangan dengan menerapkan nilai-nilai ekonomi Islam berupa shiddiq, amanah, fathonah, tabligh, 'iffah, qona'ah, adil, bijaksana, ikhlas, dan ketakwaan sehingga tercapai kesejahteraan dalam hidup dan mampu meningkatkan perkembangan ekonomi Islam. Abstract The purpose of this study was to determine behavior accounting with the Sakinah Finance approach and Islamic economic values in Islamic families. This study used a qualitative descriptive method using triangulation data analysis by combining interviews, observation, and documentation. The result of this research is that Islamic families are able to apply Behavior Accounting by recording all financial transactions by applying Islamic economic values in the form of shiddiq, amanah, fathonah, tabligh, ‘iffah, qona’ah, fair, wise, sincere, and piety so that prosperity is achieved in life and able to increase the development of the Islamic economy.